Physician Perspectives about Telemedicine: Considering the Usability of Telemedicine in Response to Coronavirus Disease 2019. Issue 1 (July 2021) - Lee, Jennifer A.; Di Tosto, Gennaro; McAlearney, Fiona A.; Miller, Steven; Mezoff, Ethan; Venkatesh, Rajitha D.; Huang, Jeannie; Lightdale, Jenifer R.; Volney, Jaclyn; McAlearney, Ann Scheck
ABSTRACT: Objective: Use of telemedicine in pediatric gastroenterology has increased dramatically in response to the coronavirus disease 2019 (COVID-19) pandemic. The goal of this study was to systematically assess the usability of telemedicine in the field of pediatric gastroenterology. Methods: The previously validated Telehealth Usability Questionnaire was distributed to physician pediatric gastroenterologist members of North American Society for Pediatric Gastroenterology Hepatology and Nutrition. Physician demographic and practice characteristics were collected. Data were analyzed using descriptive, linear mixed-effect, and ordinary least squares regression methods. Results: One hundred sixty pediatric gastroenterologists completed the survey. The majority were from academic practice (77%) with experience ranging from trainee (11%) to over 20 years of clinical practice (34%). Most (82%) had no experience with telemedicine before the pandemic. The average usability score (scale 1–5) was 3.87 (σ = 0.67) with the highest domain in the usefulness of telemedicine (μ = 4.29, σ = 0.69) and physician satisfaction (μ = 4.13, σ = 0.79) and the lowest domain in reliability (μ = 3.02, σ = 0.87). When comparing trainees to attending physicians, trainees' responses were almost one point lower on satisfaction with telemedicine (trainee effect = −0.97, Bonferroni adjusted 95% confidence interval = −1.71 to −0.23). Conclusion: Pediatric gastroenterologists who responded to the survey reported that the technology for telemedicine was usable, but trainees indicated lower levels of satisfaction when compared to attending physicians. Future study is needed to better understand user needs and the impacts of telemedicine on providers with different levels are experience to inform efforts to promote implementation and use of telemedicine beyond the pandemic. Abstract : Supplemental Digital Content is available in the text